Developing Android-Based English Learning Material - Syaifudin Latif Darmawan; Lilik Wariyanti (Intensive Journal, 2019)
This research aims to find out what the product of English materials at tenth grade of SMA N 1 Metro and to know the experts’ validation and students’ acceptability on Android-based English materials. The type of this research is Research and Development. The researcher uses ADDIE model. The subjects are 32 students in X IPS 2 class. The data collecting technique is using questionnaire and interview. The data analysis technique is descriptive analysis. The result indicates that (1) the validation of material expert I on android-based English material in content aspect obtained a total score of 94 and aspect of language obtained a total score of 96 is in a very good category. Furthermore, the result of expert II in content aspect obtained a total score of 92 and aspect of language obtained a total score of 88 is in a very good category; (2) the validation of media expert I in view aspect obtained a total score of 93 and aspect of presentation obtained a total score of 100 is in a very good category. Whereas the result of expert II in view aspect obtained a total score of 83 and aspect of presentation obtained a total score of 95 is in a very good category; (3) the students’ responses on android-based English material is in a very good category with the percentage of 96%. It can be concluded that Android-based English material is very easily to use at SMAN 1 Metro. The researcher recommends for the next researcher to develop Android-based English material with other design.